Discretionary maize policy interventions in Malawi: An impact analysis of export bans and minimum farm gate prices - Edelman, Brent (International Food Policy Research Institute, 2016)
This study assesses the efficacy of maize export bans in improving food security in Malawi and of minimum farm gate prices in increasing the incomes of Malawian smallholder farmers. It relies primarily on price and trade flow analysis using secondary data. In brief, the analysis shows that neither tool has been particularly effective in recent years in achieving their stated policy objectives. On the contrary, both maize export bans and minimum farm gate prices have been mostly non-binding or even counterproductive in their effects.